2016
DOI: 10.1080/09168451.2016.1162088
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression pattern of glucose transporters in the skeletal muscles of newly hatched chicks

Abstract: The gene expression pattern of the glucose transporters (GLUT1, GLUT3, GLUT8, and GLUT12) among pectoralis major and minor, biceps femoris, and sartorius muscles from newly hatched chicks was examined. GLUT1 mRNA level was higher in pectoralis major muscle than in the other muscles. Phosphorylated AKT level was also high in the same muscle, suggesting a relationship between AKT and GLUT1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Indeed, GLUT4 is important in insulin stimulating glucose uptake from blood in mammals . In spite of the fact that chickens are short of a GLUT4 gene, some studies reported that the insulin responsive glucose transport mechanism also exists in broilers. , Several reports revealed that the mRNA expressions of GLUT1, 3, 8, and 12 are detected in muscles and speculated that these isoforms may play a role in the insulin stimulating glucose transport in broiler chicken muscle. In the present study, CrPyr injection increased GLUT3 and GLUT8 mRNA expression levels in the breast muscle of broiler chickens at hatch. Cr supplementation could increase the GLUT4 expression in human and rat skeletal muscles. , A recent study has demonstrated that CrPyr injection enhanced the muscle Cr concentration of broilers at hatch .…”
Section: Discussionmentioning
confidence: 42%
“…Indeed, GLUT4 is important in insulin stimulating glucose uptake from blood in mammals . In spite of the fact that chickens are short of a GLUT4 gene, some studies reported that the insulin responsive glucose transport mechanism also exists in broilers. , Several reports revealed that the mRNA expressions of GLUT1, 3, 8, and 12 are detected in muscles and speculated that these isoforms may play a role in the insulin stimulating glucose transport in broiler chicken muscle. In the present study, CrPyr injection increased GLUT3 and GLUT8 mRNA expression levels in the breast muscle of broiler chickens at hatch. Cr supplementation could increase the GLUT4 expression in human and rat skeletal muscles. , A recent study has demonstrated that CrPyr injection enhanced the muscle Cr concentration of broilers at hatch .…”
Section: Discussionmentioning
confidence: 42%
“…As for mammals, glucose transport in chickens involves several glucose transporters that play a crucial role in cellular glucose uptake and glucose homeostasis. Among them, GLUT1, 3, 8, and 12 are expressed in chicken muscles (Kono et al, 2005;Coudert et al, 2015Coudert et al, , 2018Shimamoto et al, 2016), with the levels of mRNA expressions of GLUT1, 3, and 8 (but not GLUT12) being particularly high during the post-hatching period in the glycolytic Pectoralis major muscle compared to more oxidative muscles (Shimamoto et al, 2016). Moreover, although GLUT4 is the major glucose transporter in mammalian muscles, it is not expressed in chickens and the insulin-sensitive glucose transporter GLUT12 could partially play the role of GLUT4 in this species (Coudert et al, 2015(Coudert et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…To answer the growing demand for poultry meat, breeding companies have focused their efforts on improving live performances (i.e., growth rate and feed efficiency) and breast meat yield (Rauw et al, 1998;Havenstein et al, 2003a,b). The selection of meat-type chicken lines for increased growth and muscle development has been accompanied by significant anatomical, physiological, and metabolic changes.…”
Section: Introductionmentioning
confidence: 99%
“…SLC2A3 ( GLUT3 ), was classically defined as a neuronal glucose transporter due to its high level of expression and initial characterization in nervous tissue [36]. However, SLC2A3 is also highly expressed in other tissues with high energy needs, including muscle [37, 38]. The animals in the HIF group had higher expression levels of genes associated with lipid metabolism, indicating that these genes may contribute to adipogenesis and the maintenance of lipid metabolism in HIF animals.…”
Section: Resultsmentioning
confidence: 99%